TANGGUNG JAWAB NOTARIS ATAS KETERANGAN PALSU YANG DISAMPAIKAN PENGHADAP DALAM AKTA PENDIRIAN PERSEROAN TERBATAS - Aini, Nur; Simanjuntak, Yoan Nursari (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2019)
One example of a problem that brings a Notary to a claim occurs in the case of the establishment of a Limited Liability Company whose deed of establishment contains false information from the viewers. The author in this study wants to examine and analyze further about the legal consequences of the establishment of a Limited Liability Company based on false information and the form of notary accountability for the deed of establishment of a Limited Liability Company made based on false information. The research method used is normative legal research. The results of the study indicate that the establishment of a Limited Liability Company whose agreement from its founders contained a disability because a false statement could be filed against the establishment of the court to cancel the agreement to establish the Limited Liability Company. The notary in this case is neither responsible nor cannot be held accountable for the losses arising from the existence of false information on the face.Â